ADTH-04 Post colonoscopy colorectal cancer in the english national health service bowel cancer screening programme. (8th June 2018) - Derbyshire, Edmund; Nickerson, Claire; Wright, Suzanne; Morris, Eva; Moores, Billie; Valori, Roland; Rutter, Matthew D
Abstract : Introduction: PCCRC rate is a key quality indicator of colonoscopy. The Word Endoscopy Organisation has reached consensus agreement to use one method for calculating 3 year PCCRC rates (termed PCCRC-3 y) to enable benchmarking of rates. 1 This methodology, used previously by Morris et al. 2, showed a PCCRC-3 y rate of 8.6% across the English National Health Service (NHS) from 2001–2007. 2 with a rate of 7.3% in 2007. This study aimed to determine the rate of PCCRC-3 y in the English NHS Bowel Cancer Screening Programme (BCSP). Methods: Data from each colonoscopy in the BCSP is entered into a national database, the Bowel Cancer Screening System. All colorectal adenocarcinomas, within and outside the BCSP, are validated and registered by the National Cancer Registration and Analysis Service. This retrospective observational study interrogated these databases to identify those BCSP colonoscopies detecting colorectal cancers within 6 months (true positive colonoscopies) and those BCSP colonoscopies in patients who subsequently developed a colorectal cancer 6 months – 3 years after the colonoscopy (false negatives) between 2006 and 2013. Conclusions: The overall English NHS BCSP PCCRC–3 y rate from 2006–2010 is 3.1% – less than half the 7.3% PCCRC rate seen in the symptomatic English NHS for 2007, providing further evidence that high quality colonoscopy, such as that performed by screening–accredited colonoscopists in the BCSP, results in a lower rate of PCCRC. 3 4 Despite the high quality of colonoscopy in the BCSP, PCCRCs still occur, showing the importance of vigilance during all colonoscopies. Diagnosis of >2000 colorectal cancers (true positive colonoscopies) each year indicates there is an adequate sample size for annual reporting of PCCRC–3 y rate within the BCSP and comparison with PCCRC–3 yr rates in symptomatic services. References: 1. Beintaris I, et al. United European Gastroenterology Journal 5(5_Suppl):PO436. 2. Morris EJA et al. Gut 2014;0 :1–9. 3. Corley DA, et al. N Engl. J Med 2014;370 :1298–306. 4. Kaminski MF, et al. N Engl. J Med 2010;362 :1795–803.